Realization of a doped quantum antiferromagnet in a Rydberg tweezer array - Qiao, Mu; Emperauger, Gabriel; Chen, Cheng; Homeier, Lukas; Hollerith, Simon; Bornet, Guillaume; Martin, Romain; Gély, Bastien; Klein, Lukas; Barredo, Daniel; Geier, Sebastian; Chiu, Neng-Chun; et al. (Nature, 2025)
Doping an antiferromagnetic (AFM) Mott insulator is central to our understanding of a variety of phenomena in strongly correlated electrons, including high-temperature superconductors1,2. To describe the competition between tunnelling t of hole dopants and AFM spin interactions J, theoretical and numerical studies often focus on the paradigmatic t-J model3 and the direct analogue quantum simulation of this model in the relevant regime of high-particle density has long been sought4,5. Here we realize a doped quantum antiferromagnet with next-nearest-neighbour (NNN) tunnellings t′ (refs. 6-10) and hard-core bosonic holes11 using a Rydberg tweezer platform. We use coherent dynamics between three Rydberg levels, encoding spins and holes12, to implement a tunable bosonic t-J-V model allowing us to study previously inaccessible parameter regimes. We observe dynamical phase separation between hole and spin domains for |t/J| ≪ 1 and demonstrate the formation of repulsively bound hole pairs in a variety of spin backgrounds. The interference between NNN tunnellings t′ and perturbative pair tunnelling gives rise to light and heavy pairs depending on the sign of t. Using the single-site control allows us to study the dynamics of a single hole in 2D square lattice (anti)ferromagnets. The model we implement extends the toolbox of Rydberg tweezer experiments beyond spin-1/2 models13 to a larger class of t-J and spin-1 models14,15.